1994
DOI: 10.1007/bf00579699
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clodronate on established adjuvant arthritis

Abstract: The rat adjuvant arthritis model was used to study the effect of disodium clodronate on inflammation and destruction of tarsal bones and joints. Male Lewis rats were given an intradermal injection of mycobacteria. Fourteen days after immunization, rats with similar scores were assigned to the different experimental groups. They were treated subcutaneously either with saline (controls) or with clodronate at doses of 12.5 and 25 mg/kg/day five times a week for 2 weeks. Clinical signs of arthritis including the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 21 publications
2
21
0
2
Order By: Relevance
“…Therefore, the use of PA-enriched cement implants has positive effects on bone turnover and may also have some positive influence on post-operative regeneration processes. These results are in agreement with the study presented by Osterman et al (25), Francis et al (13), and Barbier et al (6), which demonstrate the antiinflammatory efficacy of both clodronate and aminobisphosphonate (pamidronate), risedronate, in established rat adjuvant induced arthritis. It was also showed that free pamidronate can suppress the proinflammatory cytokine generation more than nonaminobisphosphonates such as clodronate (26).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, the use of PA-enriched cement implants has positive effects on bone turnover and may also have some positive influence on post-operative regeneration processes. These results are in agreement with the study presented by Osterman et al (25), Francis et al (13), and Barbier et al (6), which demonstrate the antiinflammatory efficacy of both clodronate and aminobisphosphonate (pamidronate), risedronate, in established rat adjuvant induced arthritis. It was also showed that free pamidronate can suppress the proinflammatory cytokine generation more than nonaminobisphosphonates such as clodronate (26).…”
Section: Resultssupporting
confidence: 93%
“…All these factors lead to positive effect on bone formation together with enhanced growth. Some experimental in vitro and in vivo research showed a great potential of using BPs in healing of fractured bones, reducing osteoarthritis, or enhancing ingrowth of bone allografts (5,25,27). It was earlier proposed that the introduction of bisphosphonate compounds can be a very promising procedure connected with the treatment of musculoskeletal disorders in clinical practice (19,27,28).…”
Section: Resultsmentioning
confidence: 99%
“…The exact mechanism, however, needs to be established. Adjuvant-induced arthritis (AIA) is one of the most widely used animal models to study the effect of antirheumatic agents and represents a systemic inflammatory disease, with bone and cartilage changes similar to those observed in rheumatoid arthritis, but with an accelerated time span (Osterman et al, 1994). The common pathological features of adjuvant arthritis in rat and rheumatoid arthritis in humans are joint swelling associated with cellular and pannus invasion of the joint space, release of lysosomal constituents into the joint space, and bone resorption (Osterman et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant-induced arthritis (AIA) is one of the most widely used animal models to study the effect of antirheumatic agents and represents a systemic inflammatory disease, with bone and cartilage changes similar to those observed in rheumatoid arthritis, but with an accelerated time span (Osterman et al, 1994). The common pathological features of adjuvant arthritis in rat and rheumatoid arthritis in humans are joint swelling associated with cellular and pannus invasion of the joint space, release of lysosomal constituents into the joint space, and bone resorption (Osterman et al, 1994). The induction of adjuvant arthritis is thought to be due to bacterial peptidoglycan and muramyl dipeptide and occurs through cell mediated-autoimmunity by structural mimicry between mycobacteria and cartilage proteoglycans in rats (van Eden et al, 1985;Vijayalakshmi et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Despite their success in preventing systemic bone loss, however, trials with bisphosphonates in patients with RA have not demonstrated efficacy with respect to attenuating the progression of focal bone erosions (6)(7)(8)(9)(10). In contrast, results of studies in several different animal models of inflammatory arthritis indicate that bisphosphonate treatment can produce beneficial effects in both systemic bone loss and progression of focal bone erosions (3,(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%